Entering the constitutional gates with a trojan horse circumventing the paradox of political dynasties - Manalo, Maria Veronica (Philippine Law Journal, 2019)
Political dynasties have persisted perniciously in the Philippine setting. Since its prohibition clashes with the right to political participation and the right to suffrage, creating a lasting prohibition remains a difficulty. While the 1987 Constitution provides a prohibition against political dynasties, the very definition of a political dynasty and the extent of the prohibition were left for Congress to expound upon through subsequent legislation. As this leads to a lack of a clear-cut definition of a political dynasty, there remains a persisting lack of justiciable rights. The only reasonable option, therefore, is for political dynasties to be legally defined in the Constitution. However, because 70% of our legislators belong to dynastic families, a paradox is realized: the government, which so desires dynasties to end, is largely composed of dynasties. Ergo, as with previous bills that have lingered on the tables for decades, such an approach is expected to hit the wall. This paper proposes a surrender of the legislative approach and a critique of the issue through an unconventional manner. Effectively, this paper argues that the issue of political dynasties must be regarded in connection with the proper upholding of socio-economic rights, in the context of a society where corruption and patronage persist because of the people weakened by wanting to have theirfill -compromising their exercise of civil and political rights. By strengthening the enforcement of these rights, the persistence of political monopoly and their repercussions are effectively culled. Thus, we enter the Constitutional gates with a Trojan Horse: by amending the Constitution from the inside to clearly define a political dynasty and to create justiciable rights, followed by a Trojan Surprise: by strengthening the enforcement of socio-economic rights which, as far-reaching and long-term as they are, can effectively promote civil and political rights to cut the extensions of corruption and patronage that allow the profusion of political dynasties.